2017
DOI: 10.4103/ijccm.ijccm_62_17
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-acquired infection: Prevalence and outcome in infants undergoing open heart surgery in the present era

Abstract: Background:The aim of this study is to evaluate the causal relation between hospital-acquired infection (HAI) and clinical outcomes following cardiac surgery in neonates and infants and to identify the risk factors for the development of HAI in this subset of patients.Materials and Methods:After Ethics committee approval, one hundred consecutive infants undergoing open heart surgery (OHS) between June 2015 and June 2016 were included in this prospective observational study. Data were prospectively collected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A study in neonates from the USA reported that the risk factors for HAIs also included central venous catheter indwelling time >14 days and >5 postoperative blood transfusions. [ 13 ] In addition, the American Society of Anesthesiologists (ASA) score, ICU stay >48 hours, [ 2 ] the difficulty of the operation (RACHS-1 score), and cardiopulmonary bypass (CPB) time ≥200 minutes are closely related to the development of postoperative HAIs. [ 14 ] Another study from Georgia, USA reported that young patients <1 year old, emergency surgery, reoperation for any reason, reintubation, and a history of hospitalization in other hospitals within the past 3 months have also been shown to be risk factors for HAIs.…”
Section: Discussionmentioning
confidence: 99%
“…A study in neonates from the USA reported that the risk factors for HAIs also included central venous catheter indwelling time >14 days and >5 postoperative blood transfusions. [ 13 ] In addition, the American Society of Anesthesiologists (ASA) score, ICU stay >48 hours, [ 2 ] the difficulty of the operation (RACHS-1 score), and cardiopulmonary bypass (CPB) time ≥200 minutes are closely related to the development of postoperative HAIs. [ 14 ] Another study from Georgia, USA reported that young patients <1 year old, emergency surgery, reoperation for any reason, reintubation, and a history of hospitalization in other hospitals within the past 3 months have also been shown to be risk factors for HAIs.…”
Section: Discussionmentioning
confidence: 99%